Cloning and comparative analysis of zinc-finger protein gene on Y-chromosome (ZFY) between Thai Bangkaew dog and other Thai canids - Boonyaprakob, Ukadej; Homsavart, Sommai; Noosud, Jatuporn; Tungtrakanpoung, Rongdej (Agriculture and Natural Resources, 2017)
The Thai Bangkaew dog is a Spitz-type dog that originated in Thailand. Legend has it that the dog is descended from hybrids between a native female dog and a male wild canid. To examine the mysterious story about the ancestry of the Thai Bangkaew dog's paternal lineage, sequence variation was examined for the last intron of the Y-chromosome-specific zinc-finger gene, ZFY, and its X homolog for male Thai Bangkaew dogs and other male Thai canids, including the Thai ridgeback and mixed breed dogs, Asiatic jackals (Canis aureus) and a dhole (Cuon alpinus). A 1075-bp ZFY segment from DNA samples of Thai Bangkaew dogs was found to be 100% identical to the domestic dog ZFY and (if gaps are allowed) showed 81% and 92% identity to jackal ZFY and dhole ZFY, respectively. However, if gaps were treated as missing data, the 1045-bp ZFY sequence for the Thai Bangkaew dogs was 100% identical to domestic dog ZFY and 99.5% to jackal ZFY and dhole ZFY, respectively. In addition, the 959-bp Thai Bangkaew ZFX fragments were identical and showed 100% identity to domestic dog ZFX. These genetic data suggest that the Thai Bangkaew dogs still present today share a common male ancestor with modern dogs, rather than being the descendants of dhole or jackal/dog hybrids.